The Preventive Effects of Xanthohumol on Vascular Calcification Induced by Vitamin D3 Plus Nicotine - Shu-Fen Liou; Thi Tuyet Ngan Nguyen; Jong-Hau Hsu; Erna Sulistyowati; Shang-En Huang; Bin-Nan Wu; Ming-Chung Lin; Jwu-Lai Yeh (MDPI AG, 2020)
Vascular calcification (VC) is highly prevalent in patients with atherosclerosis, chronic kidney disease, diabetes mellitus, and hypertension. In blood vessels, VC is associated with major adverse cardiovascular events. Xanthohumol (XN), a main prenylated chalcone found in hops, has antioxidant effects to inhibit VC. This study aimed to investigate whether XN attenuates VC through in vivo study. A rat VC model was established by four weeks oral administration of vitamin D3 plus nicotine in Sprague Dawley (SD) rats. In brief, 30 male SD rats were randomly divided into three groups: control, 25 mg/kg nicotine in 5 mL corn oil and 3 × 105 IU/kg vitamin D3 administration (VDN), and combination of VDN with 20 mg/L in 0.1% ethanol of XN (treatment group). Physiological variables such as body and heart weight and drinking consumption were weekly observed, and treatment with XN caused no differences among the groups. In comparison with the control group, calcium content and alkaline phosphatase (ALP) activity were increased in calcified arteries, and XN treatment reduced these levels. Dihydroethidium (DHE) and 2',7'-dichloroflurescin diacetate (DCFH-DA) staining to identify Superoxide and reactive oxygen species generation from aorta tissue showed increased production in VDN group compared with the control and treatment groups. Hematoxylin eosin (HE) and Alizarin Red S staining were determined to show medial vascular thickness and calcification of vessel wall. Administration of VDN resulted in VC, and XN treatment showed improvement in vascular structure. Moreover, overexpression of osteogenic transcription factors bone morphogenetic protein 2 (BMP-2) and runt-related transcription factor 2 (Runx2) were significantly suppressed by XN treatment in VC. Moreover, downregulation of vascular phenotypic markers alpha-smooth muscle actin (α-SMA) and smooth muscle 22 alpha (SM22α) were increased by XN treatment in VC. Furthermore, XN treatment in VC upregulated nuclear translocation of nuclear factor-E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) expressions. Otherwise, Kelch-like ECH-associated protein 1 (Keap1) was alleviated by XN treatment in VC. In conclusion, our findings suggested that XN enhances antioxidant capacity to improve VC by regulating the Nrf2/Keap1/HO-1 pathway. Therefore, XN may have potential effects to decrease cardiovascular risk by reducing VC.